2018
DOI: 10.3892/etm.2018.5998
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of expression of hsa-mir-1247 and hsa-mir-1269a in ectopic pregnancy due to salpingitis

Abstract: The clinical significance of hsa-mir-1247 and hsa-mir-1269a expression in ectopic pregnancy due to salpingitis was investigated. Eighty patients with ectopic pregnancy diagnosed by ultrasonography who were admitted to Jinan Maternity and Child Care Hospital from January 2012 to May 2012 were enrolled in this study. To the observation group were assigned 35 patients whose ectopic pregnancy was due to salpingitis. The remaining 45 patients whose ectopic pregnancy was due to reasons other than endometriosis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…In support of our findings, it has been reported that serum miR-433-3p expression is upregulated in Day 19 and 24 pregnant cows [34] and during the first trimester of pregnancy in women [43]. Moreover, it has been reported that serum hsa-miR-1247-3p expression is reduced in women with ectopic pregnancy [37] and preeclampsia [39] in comparison to normal pregnant women. To further assess the accuracy of eca-miR-1247-3p, eca-miR-134-5p, eca-miR-382-5p, and eca-miR-433-3p in differentiating pregnant (25 d) from non-pregnant mares, ROC analysis was performed and indicated that eca-miR-1247-3p followed by eca-miR-134-5p retain the highest accuracy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In support of our findings, it has been reported that serum miR-433-3p expression is upregulated in Day 19 and 24 pregnant cows [34] and during the first trimester of pregnancy in women [43]. Moreover, it has been reported that serum hsa-miR-1247-3p expression is reduced in women with ectopic pregnancy [37] and preeclampsia [39] in comparison to normal pregnant women. To further assess the accuracy of eca-miR-1247-3p, eca-miR-134-5p, eca-miR-382-5p, and eca-miR-433-3p in differentiating pregnant (25 d) from non-pregnant mares, ROC analysis was performed and indicated that eca-miR-1247-3p followed by eca-miR-134-5p retain the highest accuracy.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, there has been growing interest in pregnancy-related and/or placenta-specific miRNAs in mammals [7,21,[30][31][32][33]. This interest led to the identification of several circulating miRNAs as biomarkers for early pregnancy diagnosis [34], prediction and/or diagnosis of embryonic loss [35,36], ectopic pregnancy [37,38], pre-eclampsia [39,40], intrauterine growth restriction [40,41], placental infection [41], and preterm labor [41,42]. In humans, the chromosome 14 miRNA cluster (C14MC) is one of the largest pregnancy-related miRNA clusters and consists of 52 miRNAs [21].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, miR-204-5p can inhibit angiogenesis by regulating pro-angiogenic genes such as ANGPT1 and members of the VEGF family ( 32 ). miR-1269a was found to be a risk factor for ectopic pregnancy, and currently known risk factors include assisted reproductive technologies such as in vitro artificial insemination and hormonal stimulation ( 33 ). It has also been suggested that miR-941 is expressed in trophoblast cells and involved in insulin-related intracellular signaling pathways such as Wnt signaling, phosphoinositide-3-kinase, TGF-β signaling, and PPAR-gamma ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…miR-1269a is also involved in the occurrence and progression of diseases other than cancer. For example, the high expression of miR-1269a may be a risk factor for ectopic pregnancy (Zhang et al, 2018). miR-1269a can regulate the expression of 8 downstream genes and is related to the regulation of three signaling pathways.…”
Section: Introductionmentioning
confidence: 99%